The role of cannabidiol in professional sports: a scoping review - Venn, B.; Sullivan, S. J. (New Zealand Journal of Sports Medicine, 2020)
AimThe purpose of this scoping review was to map and examine the available literature on the use of cannabidiol in professional sports. MethodsScopus, SPORTDiscus and Web of Science online databases were searched using a three different search protocols for traditional white literature purporting to the use of cannabidiol in sports for pain and/or inflammation. Grey literature was searched in a similar manner using ProQuest Dissertations & Thesis, PubMed, the Cochrane library, the World Health Organisation International Clinical Trials Registry Platform Search Portal, Australian New Zealand Clinical Trials Registry, and ClinicalTrials.gov. Records were considered for analysis if they were of any study designs including reviews and blogs pertaining to the use of cannabidiol in any sport at any level of participation, involving people of any age or gender. All texts written in english regarding any physical and/or mental health condition pertaining to pain and/or inflammation and/or recovery in a sporting context were considered. ResultsThree records were identified for inclusion from the traditional white literature search. A further 30 blog articles were selected from the grey literature search and were included in this scoping review. ConclusionThere is a vast gap in the current scientific literature supporting the use of cannabidiol in professional sports. There appears to be an ever-increasing amount of grey literature anecdotally supporting the use of cannabidiol for reducing pain, inflammation and enhancing athlete recovery. As cannabidiol is currently sold in un-regulated markets around the world, there is an urgent need for human clinical trials to determine its safety and efficacy.